2017
DOI: 10.1038/srep41755
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing doxycycline for synucleinopathies: remodelling of α-synuclein oligomers towards non-toxic parallel beta-sheet structured species

Abstract: Synucleinophaties are progressive neurodegenerative disorders with no cure to date. An attractive strategy to tackle this problem is repurposing already tested safe drugs against novel targets. In this way, doxycycline prevents neurodegeneration in Parkinson models by modulating neuroinflammation. However, anti-inflammatory therapy per se is insufficient to account for neuroprotection. Herein we characterise novel targets of doxycycline describing the structural background supporting its effectiveness as a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
86
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 60 publications
15
86
2
5
Order By: Relevance
“…These observations indicate a decrease of the concentration of low MW aSyn oligomeric species while the monomeric species concentration remains rather stable. These results are in agreement with those obtained by González‐Lizárraga et al , who observed in the presence of doxycycline a reshape of aSyn oligomers into off‐pathway and high MW species that do not evolve into fibrils. These species present a less hydrophobic surface than the on‐pathway oligomers, and they were found to reshape towards non‐toxic parallel beta‐sheet structured forms .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These observations indicate a decrease of the concentration of low MW aSyn oligomeric species while the monomeric species concentration remains rather stable. These results are in agreement with those obtained by González‐Lizárraga et al , who observed in the presence of doxycycline a reshape of aSyn oligomers into off‐pathway and high MW species that do not evolve into fibrils. These species present a less hydrophobic surface than the on‐pathway oligomers, and they were found to reshape towards non‐toxic parallel beta‐sheet structured forms .…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with those obtained by González‐Lizárraga et al , who observed in the presence of doxycycline a reshape of aSyn oligomers into off‐pathway and high MW species that do not evolve into fibrils. These species present a less hydrophobic surface than the on‐pathway oligomers, and they were found to reshape towards non‐toxic parallel beta‐sheet structured forms . This experiment demonstrates the great interest of the developed CGE–LIF method regarding the study of aSyn behavior in the presence of potentially therapeutic agents.…”
Section: Resultssupporting
confidence: 93%
“…Finally, doxycycline, a second-generation tetracycline, has shown promising neuroprotective effects in animal models of Parkinson’s disease by reducing neuroinflammation 35. Given that anti-inflammatory treatments alone have proven an inadequate preventative against neurodegeneration, González-Lizárraga et al recently investigated the capacity of doxycycline to disrupt the formation of fibrils from the accumulation of α-synuclein amyloid aggregates in neural or glial cells, a common occurrence in neurodegenerative disorders, such as Parkinson’s disease, dementia with Lewy bodies and multiple system atrophy 36.…”
Section: Case Studiesmentioning
confidence: 99%
“…Assessment of the dose–response curve indicated that the dose of doxycycline required to achieve neuroprotective effects was 20–40 mg per day, significantly lower than the 200 mg two times per day antimicrobial dose. Equally important, this subantibiotic dose is low enough that it does not induce bacterial resistance to the drug 35…”
Section: Case Studiesmentioning
confidence: 99%
“…O mecanismo de ação proposto seria através da interação da doxiciclina com os intermediários de agregação da α-sinucleína, impedindo, portanto, a formação de fibrilas de α-sinucleína. 38…”
Section: Figura 2 Estrutura 3d Do Envelope Dos Vírus (A) Chikungunyaunclassified